The Relationships Between Trait Creativity and Resting-State EEG Microstates Were Modulated by Self-Esteem - Wu, Xin; Guo, Jiajia; Wang, Yufeng; Zou, Feng; Guo, Peifang; Lv, Jieyu; Zhang, Meng (Frontiers in Human Neuroscience, 2020)
Numerous studies had found that creativity is not only associated with low effort and flexible processes, but also associated with high effort and persistent processes especially when defensive behavior being induced negative emotions. The important role of self-esteem is to buffer the negative emotions and low self-esteem are prone to instigate various forms of defensive behaviors. Thus, we thought that the relationships between trait creativity and executive control brain networks might be modulated by self-esteem. The resting-state electroencephalogram (RS-EEG) microstates can divided into four classical types (MS1, MS2, MS3 and MS4) which can reflect the brain networks as well as the dynamic characteristic of them. Thus, Williams creative tendency scale (WCTS) and Rosenberg Self-Esteem Scale (RSES) were used to investigate the modulating role of self-esteem on the relationships between trait creativity and the RS-EEG microstates. As our results showed, self-esteem consistently modulated the relationships between creativity and the duration and contribution of MS2 related to visual or imagery processing, the occurrence of MS3 related to cingulo-opercular networks, as well as transitions between MS2 and MS4 which was related to frontoparietal control networks. Based on these results, we thought that Moreover, individuals with low self-esteem might be more prone to influenced by negative emotions and develop low trait creativity; bottom-up information from vision or visual imagery might be beneficial to develop trait creativity for individuals with high self-esteem to improve trait creativity, while inhibition of irrelevant information could facilitate trait creativity for individuals with low self-esteem.